A Constellation of Roses - Asebedo, Miranda (New York, NY : HarperTeen, an imprint of HarperCollins Pubishers, 2019)
When she discovers long-lost relatives that have abilities like her own, Trix McCabe might have finally found somewhere she belongs. When her past resurfaces, she'll have to decide whether to take a chance on this new life or keep running.
Junior Library Guild
Ages 14-17.
Grades 9-12.
A Junior Library Guild selection
Keywords: Ability -- Juvenile fiction; Families -- Juvenile fiction; Fantasy fiction; Magic -- Juvenile fiction; Ability -- Fiction; Family life -- Fiction; Fantasy; Magic -- Fiction; Ability -- Fiction; Family life -- Fiction; Fantasy fiction; Magic -- Fiction; Fantasy fiction